The response of artificially aged and unaged asphalt mixes to accelerated trafficking at low temperatures - Snyman, D. R. F.(Dwight Randolph Frank),b. 1891 (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1987.